EVALUASI KEBIJAKAN PELARANGAN PEMASUKAN, PENYIMPANAN, PENGEDARAN, DAN PENJUALAN SERTA MEMPRODUKSI MINUMAN BERALKOHOL DALAM USAHA MENJAGA KELESTARIAN BUDAYA BERADAB DAERAH - Festus Ajami; Ali Hanafiah (STIA MALANG, 2020)
Currently, the local government policy, especially for the Manokwari Regency Government, is to maintainpublic order and public peace. As a commitment and consequence of the implementation of Government affairs fromthe Central Government, namely regarding one of the legal products in Regional Regulation Number 5 of 2006,concerning Policies for Supervision and Control of the Circulation of Alcoholic Drinks. Due to the development ofManokwari Regency, currently there are many criminal acts that originate from the influence of alcoholic beveragesincluding fights that take the form of persecution and domestic violence, as well as commotions that cause no peacein the population.The purpose of this study is to find out more about the Evaluation Process of the Prohibition of Importation,Storage, Distribution, and Sales and Production of Alcoholic Beverages in an Effort to Maintain the Preservation of Regional Civilized Culture in Manokwari Regency, and also to find out what are the causes or obstacles in theEvaluation process. The policy is through a qualitative research method with a descriptive approach with datacollection techniques through interviews, observation, documentation and focus discussions. Because alcohol is aprotoplasmic toxin that has a depressant effect on the nervous system, which causes a person to lose consciousnessand the ability to control himself physically, psychologically and socially, therefore policy evaluation has the task ofdetermining what consequences a policy will bring. by describing the impact and assessing the success or failure of apolicy based on predetermined standards or criteria.The policy is made so that the legal basis for the existence of a policy can be expressed as what theGovernment does to do something, whether it is an investigation of the results of a policy which is likely to show thatthe policy is in fact very different from what is implied in the policy statements, because The people of ManokwariRegency hope that with the existence of these regulations, the policies that have been made in Law Number 05 of2006, can be implemented properly, in terms of the Prohibition of Importation, Storage, Distribution, and Sales andProduction of Alcoholic Beverages in Manokwari Regency.Keywords: Policy Evaluation, Prohibition, Importation, Distribution and Production of Alcoholic Beverages,Cultural Conservation.